ANALISIS DAMPAK PELABUHAN (JIIPE) GRESIK TERHADAP POTENSI DESA MENGARE MENGGUNAKAN METODE SWOT-DELPHI - prihono, Prihono; Rifqi, Adi (WAHANA, 2017)
The development of Pelindo III (JIIPE) port of Gresik Region brings opportunities for better welfare improvement for Mengare Village community. The purpose of this study is to determine thepositive and negative impacts and potentials that can be managed and utilized optimally by MengareVillage community in an effort to improve the economy and welfare of the community. The method used isSWOT and Delphi method. Data collection techniques collected were interviews, observations,questionnaires, and documentation. The results of this study indicate that the development of Pelindo III(JIIPE) port has a positive impact that the community can work together with the government and theport in providing infrastructure and supporting infrastructure in managing the potential of the village, thecommunity can open various businesses around the port area besides the parties Ports also provideopportunities for the community in recruitment of workers in accordance with the capabilities required bythe port. While the negative impact of the port is to narrow the location of fishermen in fishing, theglobalization of the free market so that the possibility of unhealthy competition in society and thepossibility of increasing the level of unemployment in fishermen. The results of weighting the SWOTquestionnaire and the Delphi priority level decision resulted in an alternative Strength-Opportunity (SO)strategy with a weighted number of 2.30, which means using the power to opportunities exist.